Antifungal activity mode of Aspergillus ochraceus by bacillomycin D and its inhibition of ochratoxin A (OTA) production in food samples. (February 2016) - Qian, Shiquan; Lu, Hedong; Sun, Jing; Zhang, Chong; Zhao, Haizhen; Lu, Fengxia; Bie, Xiaomei; Lu, Zhaoxin
Abstract: The inhibition effects of bacillomycin D on the growth of Aspergillus ochraceus and the production of ochratoxin A (OTA) in food samples were investigated. The mycelia growth and sporulation were completely inhibited by 30 μg/mL of bacillomycin D. Microscopic morphological changes such as the distortion of hyphae and the disruption of spores at 20 μg/mL of bacillomycin D were significantly observed. The use of bacillomycin D resulted in cell damage, nucleic acids and proteins divulge, and more production of reactive oxygen species (ROS), and all these factors actively contributed to the promotion of apoptosis of A. ochraceus . In addition, 90 μg/g of bacillomycin D completely inhibited the growth of A. ochraceus and the production of OTA in food samples. Our results suggested that bacillomycin D showed a significant antifungal activity against A. ochraceus that could be used as a potential natural antimicrobial to control food contamination and ensure food safety. Highlights: Bacillomycin D exhibits strong antifungal activity against Aspergillus ochraceus. Hyphal distortion and sporular disruption of A. ochraceus occurs by bacillomycin D. Bacillomycin D significantly induces cell apoptosis of A. ochraceus. Bacillomycin D inhibits OTA production in food samples.